A diary study of Australian lawyers working with traumatic material. Issue 4 (4th July 2022) - Weir, Patricia; Jones, Liz; Sheeran, Nicola; Kebbell, Mark
Abstract : Many lawyers experience regular exposure to traumatic material yet little is known about its effects. This study examines what traumatic material affects lawyers, how they respond in the moment and how they recover. The participants ( n  = 18 lawyers) completed a five-day diary study and a semi-structured interview regarding their experiences. The analysis identified clients' negative emotions and experiences, domestic violence and child abuse as most impactful. The participants reported experiencing sadness, anger, frustration, disgust and/or compassion; some reported not being overly distressed or not experiencing emotions. Most participants reported using social support and emotion-focused coping strategies, drawing on their identities as lawyers to suppress or conceal emotions. At the end of a working day many participants reported coping by working longer hours but also through physical activity and social interactions. We discuss the implications for lawyers' well-being and the role of organisations and education in managing the impacts of traumatic material.